The Covid-19 Pandemic and its Effect on the Elderly: A Review - Nadri, Maimoona; Zubair, Ujala (Open Science Journal, 2020)
In 2019, the world experienced a global public health concern when the novel coronavirus originated from China and affected around fifty-seven thousand people around the world by March 2020. The quick rise in the number of cases and the death toll overwhelmed the scientific and medical community. While all the focus was driven towards finding the epidemiology, the treatment and the management, the mental health aspect of the quarantine was being overlooked. The purpose of this review is to create awareness about the long-term consequences of quarantine, with the focus on the elderly community in Pakistan.